Law & Psychiatry: Regulating Psychotherapy or Restricting Freedom of Speech? California’s Ban on Sexual Orientation Change Efforts - Appelbaum, Paul S (Psychiatric services (Washington, D.C.), 2014)
A 2012 California law banning treatment to change the sexual orientation of patients under 18 years old marked the first time a state has restricted the practice of a specific psychotherapy. Practitioners of the therapy sued, arguing that the ban violated their free speech, but the State of California claimed that the statute was one of many ways that it regulates the practices of the health professions. The law may have opened the door to some unintended consequences, according to the Law & Psychiatry column. California’s new law banning sexual orientation change efforts by licensed therapists for patients under 18 immediately provoked court challenges. Therapists, parents, and patients argued that the statute infringed constitutional rights to freedom of speech and parental rights to select treatments for their children. The U.S. Court of Appeals for the Ninth Circuit rejected all of these claims in a unanimous decision upholding the law. However, the decision evokes concerns that other forms of psychotherapy could be subject to similar regulation. Tort remedies may provide less intrusive means for discouraging use of ineffective and potentially harmful therapies.